Microstructure of Aluminum Alloys: Effect of Hardening Conditions - Demiroren, Fliilya (Crc Press-Taylor & Francis Group, 2019)
In the present article, aluminum and its heat treatments were expressed. Also it was investigated that the influence of quenching type after solutizing heat treatment of cast Al-8.88Si-3.38 Cu on the microstructure has been reported. Alloys were prepared by controlled melting and casting. All the alloys were solutionized at 525 degrees C for 4 h followed by water quenching at 65 degrees C for 1, 15, 30, 60, and 90 min, respectively, and aged at 175 degrees C for 4 h. Then they were cooled at room temperature. It was performed SEM-EDX analysis and X-ray analysis. From the analysis, it was determined Al2Cu and Al7FeCu2 phases. It was determined that those phases reinforce the microstructure. As a result, the type of quenching after solution treatment is very important for aluminum alloys.
Keywords: Aluminum alloys; Hardness; Quenching; Solution heat treatment